A Content Analysis of Career Adaptability Among Marine Cadet - Wiwik Sulistiani; Dewi Retno Suminar; Wiwin Hendriani; Suryanto Suryanto (Universitas Ahmad Dahlan, 2021)
Career adaptation is important for individuals, especially for individuals who are preparing for a future career. The purpose of this study is to describe the career adaptation of marine cadets and discuss the factors supporting the adaptation of marine cadet careers. Research respondents were marine education cadets in Surabaya, Indonesia. Data analysis used content analysis. Marine cadets that show the four dimensions of career adaptation are 58%. In addition, the results of the study showed that the highest supporting factors for career adaptation were parents, and the biggest inhibiting was the cadets themselves. Cadets feel irritable, bored, and feel don't have enough time to study. Cadets also feel the demands of high duties during education. Further research is needed related to internal and external factors that affect career adaptability.